ANALISIS RASIO KEUANGAN DAN PENGARUHNYA TERHADAP PROFITABILITAS BANK SYARIAH DI INDONESIA - Kinkin Wardani; Pani Akhiruddin Siregar; Kadri Bancin (Jurnal At-Tabayyun, 2019)
Research aims to test the analysis of financial ratios and influence on the profitability of Sharia Banks in Indonesia. The analysis indicators of financial ratios include CAR, NPF, FDR and BOPO. The profitability indicators of Sharia Banks in Indonesia are ROA. The research method uses a quantitative approach with multiple linear regression analysis techniques. Data used secondary data in the form of a monthly time-series data from the Financial Report of Sharia Commercial Bank and Sharia Business Unit published by Sharia Banking Directorate, Bank Indonesia and the Bank Licensing and Banking Information Department, Indonesia Financial Services Authority through Sharia Banking Statistics Bank Indonesia/Indonesia Financial Services Authority from January 2006 to January 2018. The following research results: (1) The result of the model estimate shows its R Square value of 0,610 representing the value of coefficient of determination. This means that 61% of the variable variations of the ROA are capable of being described by independent variable in this model. The remaining 39% is explained by other reasons that do not fit into the model; (2) A regression model on the independent variable simultaneously affects the dependent variable, so that the independent variable regression model can be used to predict the dependent variable; and (3) CAR, NPF and FDR have a direct and significant relationship with ROA. BOPO also has a direct relationship with ROA. However, it is not significant.